THE INFLUENCE OF SELF AWARENESS ON MATHEMATICS LEARNING OUTCOMES OF CLASS VII STUDENTS OF SMP NEGERI 1 BUNTAO' - Duma', Sonny Yalti; Tandiseru, Selvi Rajuaty; Tandioga, Rispa (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
One thing that influences learning outcomes is self-awareness. Self-Awareness (is an ability that allows students to adapt self with person other with increase control himself, can understand other people, and can learn to achieve a goal. The aim of this study to determine whether there is an influence of self-awareness on learning outcomes mathematics class VII students of SMP Negeri 1 Buntao'. The population of this study were students Class VII of SMP Negeri 1 Buntao'. Sampling used cluster techniques random sampling so class VII B was selected as a research sample. (1) Method collection data use questionnaire Which use scale Likert and documentation in the form of final semester exam scores. The analysis technique used is Analysis Statistics descriptive, analysis statistics inferential. (2) Test precondition analysis form test normality, test linearity and test hypothesis. Technique analysis and test precondition use program SPSS 21. (3) Results study show that there is Self-Awareness in learning mathematics with mathematics learning outcomes student class VII JUNIOR HIGH SCHOOL Country 1 Buntao'. Matter This proven with mark t count > t table (4,193 >2,056).